The Influence of Leadership Style, Work Stress, and Work Motivation on Employee Loyalty to PT. Hartono Palace of Technology - Johanis Souisa; Teguh Ariefiantoro; Susanto Susanto; Asih Niati (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2023)
This study aims to analyze the effect of style, leadership, work stress, and work motivation on employee loyalty at PT. Hartono Istana Teknologi. This study uses the variables of leadership style, work stress, and work motivation as independent variables and employee loyalty as the dependent variable.The population of this study were warehouse employees at PT. Hartono Istana Teknologi with a population of 435 employees. With a sample of 81 employees using purposive sampling method (sample with criteria). The data analysis method used in this research is multiple linear regression.The result of this study prove that the leadership style variable has a positive significant influence on employee loyalty, the work stress variable has a positive significant influence on employee loyalty, work motivation has a positive significant influence on employee loyalty.